Critical Discourse Analysis on Komik Kita Comic Strip: Another Attempt at Political Propaganda - Putra, Rizky Anugrah (Yayasan Kyadiren, 2022)
The rapid dissemination of knowledge through information technology is facilitated by expanding access, but this development has drawbacks due to political interests. One of the media used to spread propaganda that promotes polarization is comics. The researcher analyzes how popular comics mix provocative discourses to influence their readers and what themes they adopt. Using critical discourse analysis, the researcher examines three main dimensions of propaganda discourse production, dissemination, and impact in comics. The data analyzed includes 1237 comic strips by Komikkita, of which 87% contain political propaganda, and 10.9% contain propaganda that targets followers of a particular religion. The study suggests that comic writers carry out the mission of a particular group through their media, indicating that discourse cannot be separated from the motives and values that the discourse architect wants to disseminate. This finding supports the elementary theory of discourse initiated by Van Dijk.